Systematic review of psychological and sociocultural factors influencing the adaptation of students participating in international academic mobility (Jóvenes en la Ciencia, 2026)
The aim of this article is to identify and understand the psychological, social, and cultural factors that influence the adaptation process of students participating in international academic mobility. To this end, a systematic review of scientific publications from 2010 to 2023 was conducted. The following search terms were used: “acculturation,” “psychological adaptation,” “social adaptation,” “intercultural adaptation,” “international students,” “psychological predictors,” and “support networks.” The scientific databases consulted were LILACS, Dialnet, PubMed, Scielo, Redalyc, and national and international university repositories. After applying inclusion and exclusion criteria, 15 articles were retrieved. Analysis of these articles shows that integration stands out as the most effective strategy in the adaptation process of students experiencing international academic mobility. It is also considered a strategy that promotes well-being. In turn, language proficiency is a fundamental factor, and a lack thereof can hinder the adaptation process for students. Likewise, social support (from peers, compatriots, and local people) influences the success that can be achieved in the adaptation process. Relationships with locals can also contribute to reducing anxiety and improving cultural understanding. At the same time, culture shock is common and requires strategies such as resilience and rational coping. The cultural similarity between the country of origin and the host country can facilitate the students' adaptation process. It is noteworthy that among the main personal benefits that international academic mobility has for students is its contribution to autonomy, confidence, and personal growth. It is concluded that due to the various contributions of academic mobility, it is important to promote this experience among the university and scientific community.